Impact of BMI and Gender on Outcomes in DLBCL Patients Treated with R-CHOP: A Pooled Study from the LYSA. (16th January 2014) - Sarkozy, Clémentine; Mounier, Nicolas; Delmer, Alain; Van Hoof, Achiel; Karsenti, Jean Michel; Fleck, Emmanuel; Maerevoet, Marie; Eisenmann, Jean Claude; Delarue, Richard; Fabbro, Michel; Coiffier, Bertrand
Abstract : In diffuse large B-cell lymphoma (DLBCL), the age-adjusted International Prognostic Index (aaIPI) score is currently used to predict patient outcomes and to choose the best therapeutic treatment. Body mass index (BMI) and gender are occasionally sited as prognostic factors; however, their value has never been studied in a large series of patients included in prospective clinical trials in the rituximab era. To assess the impact of BMI and gender on OS and PFS independently of the aaIPI score, we pooled 985 patients that were prospectively included in GELA studies and uniformly treated with R-CHOP. Univariate analysis indicated that high aaIPI and male gender were associated with a worse PFS, whereas high (>25) or low (<18.5) BMI scores were not. High aaIPI score was the only factor predictive for OS. In a multivariate analysis, including aaIPI score, gender, BMI, and interaction between BMI and gender, aaIPI remained the strongest predictive factor, and BMI < 18.5 was significantly associated with a worse OS but not PFS. In conclusion, in the rituximab era, the aaIPI score remains the major predictor of outcome in DLBCL patients; however, male gender and low BMI seem to impact outcome.